PERSEPSI MASYARAKAT TERHADAP ASURANSI, KASUS GAGAL BAYAR, DAN PROGRAM PENJAMINAN POLIS ASURANSI - Ni Ketut Budiningsih; I Wayan Priyana Agus Sudharma; Made Sinthya Aryasthini Mahaendrayasa; Diah Pradnyadewi T; Ida Ayu Intan Rahmanti (Yayasan Nusantara Hasana Berdikari, 2026)
Insurance policy ownership data has experienced a downward trend from year to year. The occurrence of insurance default cases is thought to have reduced consumer trust in insurance services. Therefore, the Policy Protection Program (PPP) is expected to be able to restore public trust. This study aims to analyze public perceptions regarding insurance policy ownership. This study also analyzes how default cases that occur affect public trust. In the final stage, this study analyzes consumer perceptions regarding PPP. This study uses a qualitative research method in primary data analysis. The scale used is the Likert Scale. The results are that public perceptions regarding insurance policy ownership are influenced by public perception, level of trust, financial literacy, and risk analysis.